A Review of the Risk Factors Associated With Poor Outcomes in Patients With Coronavirus Disease 2019 - Hanif, Muhammad (Cureus, 2020)
The global pandemic of coronavirus disease 2019 (COVID-19) and its rapid spread throughout the globe is of much concern. With little known about the peculiar virus and the changing mortality and morbidity, we attempt to review the risk factors associated with significant outcome.  We conducted a review of the information available in medical journals published on COVID-19 risk factors associated with poor outcomes using PubMed®, Google Scholar, and material published online. The risk factors associated with poor outcome were kept in particular consideration. A total of 96 articles were thoroughly reviewed and analyzed so as to highlight the risk factors and the subsequent disease presentation that were present in patients with COVID-19. With little data available in this regard, emphasis and consideration of risk factors might help health care workers preclude the worst outcome. From the aforementioned search we can conclude that the most prevalent risk factors were reported to be hypertension followed by diabetes. In terms of mortality, age greater than 65 was the most significant risk factor. Among non-survivors, coagulation profile including d-dimers, prothrombin time, and inflammatory markers like erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and serum ferritin levels were very deranged. Much emphasis and consideration in relation to risk factors must be deliberated by health care workers so as to prevent severe outcomes and mitigate appropriate treatment modalities.